2010
DOI: 10.1002/eji.201040428
|View full text |Cite
|
Sign up to set email alerts
|

Dichotomy between factors inducing the immunosuppressive enzyme IL‐4‐induced gene 1 (IL4I1) in B lymphocytes and mononuclear phagocytes

Abstract: MU and DC are key elements in the control of tissue homeostasis and response to insult. In this work, we demonstrate that MU and DC are the major producers of the phenylalanine catabolizing enzyme IL-4-induced gene 1 (IL4I1) under inflammatory conditions. IL4I1 was first described in B cells, which indeed can produce IL4I1 in vitro, although at much lower levels. In vivo, IL4I1 is highly expressed by MU and DC of Th1 granulomas (sarcoidosis, tuberculosis) but poorly detected in Th2 granulomas (schistosomiasis)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 27 publications
9
69
0
Order By: Relevance
“…Although many aspects of the molecular pathway involved in the IL-17A production are still unknown, it has been shown that the activation of NF-kB family members RelA and RelB is essential for the regulation of IL-17A expression in mice gd T cells (Powolny-Budnicka et al, 2011) and that IKKa selectively associates with IL17A locus, inducing its transcriptional activation . In addition, it has been shown that IL4I1 mRNA expression is regulated by NF-kB pathway (Julià et al, 2007;Marquet et al, 2010). These findings are in keeping with the observation reported in the present study showing that NFKB1 and RELA mRNA expression and NFkBp65 phosphorylation were not altered in Th17 cells when compared to Th1 cells.…”
Section: Discussionsupporting
confidence: 94%
“…Although many aspects of the molecular pathway involved in the IL-17A production are still unknown, it has been shown that the activation of NF-kB family members RelA and RelB is essential for the regulation of IL-17A expression in mice gd T cells (Powolny-Budnicka et al, 2011) and that IKKa selectively associates with IL17A locus, inducing its transcriptional activation . In addition, it has been shown that IL4I1 mRNA expression is regulated by NF-kB pathway (Julià et al, 2007;Marquet et al, 2010). These findings are in keeping with the observation reported in the present study showing that NFKB1 and RELA mRNA expression and NFkBp65 phosphorylation were not altered in Th17 cells when compared to Th1 cells.…”
Section: Discussionsupporting
confidence: 94%
“…IL4I1 is normally activated by the IL4 receptor via STAT6. The expression of IL4I1 is regulated by NF-B signaling through the activation of B-cells through the CD40 pathway (29). Accordingly, we find the glycosites of CD40 as well as CD80, the two receptors required for T-cell dependent activation, also up-regulated in the ABC subtype.…”
Section: Segregation Of Dlbcl Subtypes Based On Glycopeptide Signaturmentioning
confidence: 67%
“…Accordingly, IL4I1 is highly expressed in Th1 but not in Th2 granulomas. This enzyme has also been detected in B lymphocytes following activation by IL-4 and CD40, although at much lower levels [2]. At physiological pH and temperature, IL4I1 degrades the essential amino acid phenylalanine (Phe), producing phenylpyruvate, H 2 O 2 and ammonia.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new fish LAAO has been described, which may contribute to the innate immune defense against a variety of bacteria and protozoans [10]. As IL4I1 expression is induced in mononuclear phagocytes by pathogen-derived signals, such as Toll-like receptor ligands [2], it may participate in the innate immune defense against pathogens in mammals, in addition to its regulatory effects on the specific immune response.In this work, we thus evaluated the effect of recombinant IL4I1 on Gram-positive and Gram-negative bacteria growth. We show that IL4I1 can act as an antibiotic, which could potentially contribute to the arsenal used by activated macrophages to generate an extracellular environment hostile to bacterial growth.…”
Section: Introductionmentioning
confidence: 99%